Measuring globalization: A hierarchical network approach - David Matesanz Gomez; Guillermo J. Ortega; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2011)
This paper investigates the business cycle co-movement across countries and regions since the middle of the last century as a measure for quantifying the ongoing globalization process of the world economy. Our methodological approach is based on analysis of a correlation matrix and the networks it contains. Such an approach summarizes the interaction and interdependence of all elements and it represents a more accurate measure of the global interdependence involved in the economic system. Our results show (1) that the dynamics of globalization has been more driven by synchronization in regional growth patterns than by the synchronization of the world economy as a whole in contrast with other empirical works and (2) that world crisis periods increase dramatically the global co movement in the world economy.
Keywords: E32; C45; O47; 330; Globalization; regionalism; correlation matrix; clustering; synchronization